Descriptive Study of The Implementation of Electronic Medical Records on Insurance Claims at PKU Muhammadiyah Gombong Hospital - Ahmad Fatoni Dwi Julian; Sali Setiatin (Dinasti Information and Technology, 2025)
The implementation of Electronic Medical Records at PKU Muhammadiyah Gombong Hospital is one of the steps in improving service quality in line with the times in the digitalization era, particularly in insurance claims. The purpose of this study is to understand how the implementation of electronic medical records is carried out in insurance claims at PKU Muhammadiyah Gombong Hospital. The method used in this study is a descriptive study using data collection techniques through observation, interviews, and documentation. The study results show that the implementation of electronic medical records can speed up patient data input, minimize administrative errors, and facilitate the insurance claim process. The staff have adequate competence in operating the system, although there are still issues with internet connectivity and system speed. This study concludes that EMR plays an important role in patient services and makes the insurance claim process more efficient, while emphasizing the importance of system stability. Periodic training for staff and communication with the insurance company to ensure a smooth insurance claim process